Analysis of Carbon Reduction Strategy on Distributed Combined Cooling, Heating and Power (CCHP) Systems Design in Rural Area. (May 2018) - Zhu, Y; Shao, B; Tong, Q L; Liu, Y F; Li, Y X; Yan, X X; Wu, N; Du, T
Abstract: An optimal design model of distributed CCHP systems is established based on the minimum system cost. Renewable energy is added as auxiliary energy. By proposing carbon emission reduction constraints, the influence for optimal design of the system could be analysed, which generated by the changes in carbon emission reduction rate. Some reasonable results would be achieved, such as: 1. A trade-off among system cost, building energy consumption and carbon emission reduction can be received, and optimization schemes under different carbon emission reduction strategies are obtained. 2. System lowest carbon reduction rate is 20%, and the highest is 50%; systems lowest primary energy saving rate is 4.91%, and the highest is 19.09%. 3. With the change of carbon emission reduction strategy, energy consumption and costs of the distributed CCHP systems show diversity differences at the same time. This article suggests the carbon emission reduction rate of CCHP systems is 40% in Ankang rural.